Gender Justice Actualization through Gender Islamic School - Muhammad Izzul Haq; Mochammad Najmul Afad (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
The Islamic School and Gender (SIG) is the first formal cadre of the Women’s Indonesian Islamic Student Movement Corps (PMII) after participating in the acceptance of new members organized by the Indonesian Islamic Student Movement to provide an understanding of the Islamic perspective in responding to gender issues. This study uses qualitative methods with interviews and participatory observations and documentation techniques as data collection techniques. The results show the Islamic School and Gender (SIG) organized by PMII convey the values ??of gender equality, mubadalah (mutuality), and partiality to women. Recommendations for this research are given to educational institutions that become places of gender equality socialization to make Islamic and Gender Schools as sone reference for students or young people to study Islam and gender.